High‐performance copoly(benzimidazole‐benzoxazole‐imide) fibers: Fabrication, structure, and properties. Issue 22 (12th February 2015) - Luo, Longbo; Zheng, Yaxin; Huang, Jieyang; Li, Ke; Wang, Huina; Feng, Yan; Wang, Xu; Liu, Xiangyang
ABSTRACT Novel high‐performance copolyimide (co‐PI) fibers containing benzimidazole and benzoxazole ring in the main chain were prepared by a two‐step spinning via the poly(amic acid)s. Effects of the incorporated benzimidazole and benzoxazole units on the micro‐structure and properties of co‐PI fibers were investigated. Fourier transform infrared (FTIR) results indicated that hydrogen bonding is formed in the co‐PI fibers. The co‐PI fibers exhibited discernible crystallization peaks at 14°∼15° and 23°∼26° (2θ), showing crystalline‐like structure. Moreover, the packing type of benzimidazole‐imide units determined the macromolecules packing of co‐PIs. It was amazedly found that the co‐PI fibers exhibited higher tensile strength and initial modulus than those of corresponding homo‐PI fibers, reaching tensile strength of 2.2–2.6 GPa, initial modulus of 99.1–113.2 GPa. The results of dynamic mechanical analysis (DMA) indicated co‐PI2 fiber had a positive Tg deviation due to the presence of strong intermolecular hydrogen bonding between benzimidazole‐imide and benzoxazole‐imide units, which maybe lead to the effective stress transfer between benzimidazole‐imide units and benzoxazole‐imide units. In addition, the obtained PI fibers exhibited excellent thermal properties with the 10% weight loss temperatures under N2 in the range of 574–585°C. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42001.